Aquatic macroinvertebrate colonization of artificial substrates in low-order streams - Leite-Rossi, Luciene Ap. (2015)
One of the factors that determine the presence and establishment of the benthic biota in aquatic ecosystems is the nature of the available substrate. The colonization of artificial substrates for macroinvertebrates has often been used as a tool in environmental assessments by operating facilities it provides. The present study aimed to determine whether or not macrofauna exhibit selectivity for different types of artificial substrates. Colonization recipients containing different substrates were immersed in three small streams in the region of São Carlos, São Paulo, for 30 days. To evaluate selectivity for each substrate type, a comparison was made between the colonizing and resident fauna in each stream. Data analysis indicated that macroinvertebrate fauna exhibited selectivity for different artificial substrate types in the streams studied. These results point to the need for knowledge of water body characteristics prior to study (e. g., types of substrates in stream beds and surrounding vegetation, etc.) in order to choose the types that are better colonized by specific groups of macroinvertebrates.